2006
DOI: 10.1007/s00256-006-0146-9
|View full text |Cite
|
Sign up to set email alerts
|

Magnetization transfer analysis of cartilage repair tissue: a preliminary study

Abstract: The differences between damaged and repaired cartilage MTR are too small to enable MT-imaging to be a useful tool for postoperative follow-up of cartilage repair procedures. There is, however, an evolution towards normal MTR-values in the cartilage repair tissue (especially after ACI repair).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 21 publications
2
13
0
Order By: Relevance
“…They also explain that the high MTR not only depended on collagen content but may also reflect a number of other parameters 46. In our study, the MTR values were 35.8%±4.2%, 36.1%±3.2%, and 35.4%±3.8%, respectively, which are similar to the MTR values in normal cartilage reported by Palmieri et al19 and Welsch et al21 but far different than the reported values of 85%–86%, ±1%, by Stanisz et al47 and Yao et al26 (Tables 1 and 2). In our present study, no significant differences were found among these three groups regarding MTR (Table 2), which is similar to in Welsch et al21 who considered that T2 decreases with T1 increases may counterbalance their effects on the MT contrast achieved with Steady-State Free Precession at 7 T. The changes in MTR likely reflect the changes in collagen structure, rather than collagen concentration 48.…”
Section: Discussionsupporting
confidence: 90%
“…They also explain that the high MTR not only depended on collagen content but may also reflect a number of other parameters 46. In our study, the MTR values were 35.8%±4.2%, 36.1%±3.2%, and 35.4%±3.8%, respectively, which are similar to the MTR values in normal cartilage reported by Palmieri et al19 and Welsch et al21 but far different than the reported values of 85%–86%, ±1%, by Stanisz et al47 and Yao et al26 (Tables 1 and 2). In our present study, no significant differences were found among these three groups regarding MTR (Table 2), which is similar to in Welsch et al21 who considered that T2 decreases with T1 increases may counterbalance their effects on the MT contrast achieved with Steady-State Free Precession at 7 T. The changes in MTR likely reflect the changes in collagen structure, rather than collagen concentration 48.…”
Section: Discussionsupporting
confidence: 90%
“…Higher RF power accompanies the problem with SAR, so quantitative MT techniques have been studied in a limited number of human studies (281284). Therefore, most studies have been conducted using tissue samples (283, 285290) or animal models (291293) and have shown that MT is affected mostly by the collagen content and changes in collagen-water interaction.…”
Section: Magnetization Transfermentioning
confidence: 99%
“…24 Cartilage T2 mapping at 1.5-T MR imaging shows promise as a noninvasive tool to study and differentiate cartilage composition after surgical cartilage repair procedures. 26 One MRI technique, magnetization transfer (MT) imaging, 27 is known to generate a useful image contrast in cartilage in vitro, which is sensitive to the macromolecular content of the cartilage. Palmieri and coworkers 27 have studied cartilage repair with microfracture, comparing the repair with autologous chondrocyte implantation (ACI) repair.…”
Section: T2-weighted (Dual) Fast Spin Echo (Fse) Techniques With or Wmentioning
confidence: 99%
“…26 One MRI technique, magnetization transfer (MT) imaging, 27 is known to generate a useful image contrast in cartilage in vitro, which is sensitive to the macromolecular content of the cartilage. Palmieri and coworkers 27 have studied cartilage repair with microfracture, comparing the repair with autologous chondrocyte implantation (ACI) repair. The differences between damaged and repaired cartilage magnetization transfer ratio (MTR) were too small to enable MT imaging to be a useful tool for postoperative follow-up of cartilage repair procedures.…”
Section: T2-weighted (Dual) Fast Spin Echo (Fse) Techniques With or Wmentioning
confidence: 99%
See 1 more Smart Citation